The correlation between generalized joint hypermobility and musculoskeletal disorders in female dancers - Putri Nadila Sari; Ni Luh Putu Gita Karunia Saraswati; I Made Niko Winaya; I Made Ady Wirawan (Physical Therapy Journal of Indonesia, 2024)
Background: Bali is a popular tourist destination because of its unique culture. One of its unique features is the Balinese dance, which is used to welcome guests, perform arts, and perform religious ceremonies. Many Balinese dancers experience generalized joint hypermobility (GJH) without realizing it, which may have a negative impact on them, especially if they have a problem of musculoskeletal pain. Methods: This research used an analytical observational design of a cross-sectional study. This study employed the sampling technique of purposive technique with a total sampling method. The inclusion criteria for this study were traditional Balinese dancers living in Denpasar city, female, aged 14-20, and having dancing experience more than 1 year. Exclusion criteria were subjects after surgery for fractures or other musculoskeletal injuries in the upper or lower extremities, subjects with signs of acute inflammation in the joints, and those unwilling to be research subjects. The number of samples was calculated using the lame show formula, and 85 samples were obtained. Data was collected by measuring GJH and musculoskeletal disorders using the Nordic body map questionnaire. Results: Based on the bivariate analysis test with Spearman's rho, p-value = 0.000 (p < 0.05) was obtained for the two independent variables with a correlation coefficient of r = 0.797. Conclusion: Based on the research results, it can be concluded that there is a relationship between GJH and MSDs in the Balinese dancer population in Denpasar City.